Source limitation drives slow compositional recovery in tropical secondary forests - Luísa Genes; Amanda Wendt; Bryan Finegan; Cristina Barber; Diego Delgado; Marta Peláez; Nohemi Huanca Nunez; Richard K. Kobe; Rodolfo Dirzo; Robin L. Chazdon (Proceedings of the National Academy of Sciences, 2026)
Tropical forests can recover diversity, structure, and function rapidly after disturbance. However, plant compositional recovery remains incomplete even after many decades, and the reasons for this lag are poorly understood. We investigated the roles of source, dispersal, and establishment limitation in affecting compositional recovery in Costa Rican forests using long-term data on species composition of trees, seeds, seedlings, and saplings, along with measurements of herbivory and leaf pathogen damage in seedlings and saplings from old-growth (OG) and second-growth (SG) forest plots. We classified tree species into successional groups, including: generalist (similar relative abundance in OG and SG), old-growth specialist (higher relative abundance in OG), old-growth exclusive (detected only in OG), and too rare to classify conclusively. Infrequent species drove community dissimilarity between old-growth and second-growth plots, and 40% of species in old-growth plots were absent as trees in second-growth forests up to 55 y old. Old-growth exclusive species (as trees and seedlings and saplings in OG plots and as seeds in seed traps in OG and SG) have extremely low abundance (11 trees/ha; 1 seedling or sapling/ha; 8 seeds/ha), indicating strong source limitation. Old-growth exclusive species shared seed dispersal traits with old-growth specialists established in SG, providing no evidence of dispersal limitation. Old-growth specialist seedlings and saplings had higher survival in SG than in OG, providing no evidence of establishment limitation. These findings suggest source limitation as the primary driver of delayed compositional recovery in mid-to-late stages of forest succession and underscore the potential for targeted enrichment plantings to accelerate full compositional recovery.